Effects of the LPA1 Receptor Deficiency and Stress on the Hippocampal LPA Species in Mice - Tabbai, Sara; Moreno-Fernández, Román Dario; Zambrana-Infantes, Emma; Nieto-Quero, Andrea; Chun, Jerold; García-Fernández, Maria; Estivill-Torrús, Guillermo; Rodríguez de Fonseca, Fernando; Santín, Luis Javier; Oliveira, Tiago Gil; Pérez-Martín, Margarita; Pedraza, Carmen (Frontiers in Molecular Neuroscience, 2019)
Lysophosphatidic acid (LPA) is an important bioactive lipid species that functions in intracellular signaling through six characterized G protein-coupled receptors (LPA1–6). Among these receptors, LPA1 is a strong candidate to mediate the central effects of LPA on emotion and may be involved in promoting normal emotional behaviors. Alterations in this receptor may induce vulnerability to stress and predispose an individual to a psychopathological disease. In fact, mice lacking the LPA1 receptor exhibit emotional dysregulation and cognitive alterations in hippocampus-dependent tasks. Moreover, the loss of this receptor results in a phenotype of low resilience with dysfunctional coping in response to stress and induces anxiety and several behavioral and neurobiological changes that are strongly correlated with mood disorders. In fact, our group proposes that maLPA1-null mice represent an animal model of anxious depression. However, despite the key role of the LPA-LPA1-pathway in emotion and stress coping behaviors, the available information describing the mechanisms by which the LPA-LPA1-pathway regulates emotion is currently insufficient. Because activation of LPA1 requires LPA, here, we used a Matrix-Assisted Laser Desorption/ Ionization mass spectrometry-based approach to evaluate the effects of an LPA1 receptor deficiency on the hippocampal levels of LPA species. Additionally, the impact of stress on the LPA profile was also examined in both wild-type (WT) and the Malaga variant of LPA1-null mice (maLPA1-null-mice). Mice lacking LPA1 did not exhibit gross perturbations in the hippocampal LPA species, but the LPA profile was modified, showing an altered relative abundance of 18:0 LPA. Regardless of the genotype, restraint stress produced profound changes in all LPA species examined, revealing that hippocampal LPA species are a key target of stress. Finally, the relationship between the hippocampal levels of LPA species and performance in the elevated plus maze was established. To our knowledge, this study is the first to detect, identify and profile LPA species in the hippocampus of both LPA1-receptor null mice and WT mice at baseline and after acute stress, as well as to link these LPA species with anxiety-like behaviors. In conclusion, the hippocampal LPA species are a key target of stress and may be involved in psychopathological conditions.